Delay spread estimation using a game engine ray based model in indoor scenario at 5 GHz (2016)
In this paper we show the results of a simulation of channel parameters using a Game Engine Ray based tool, developed by our group, which has been evolving during last few years. We show simulation results and compare it with a set of measurements for an indoor scenario, in the band of 5.4 GHz. We found a good match between the rays based tool and measurements for Delay Spread. Also, we show the use of an Open Source 3D modelling tool for the scenario building, showing the flexibility of the XML description language for this kind of scenarios.